2020
DOI: 10.3390/plants9091235
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Analysis of SRO Gene Family in Chinese Cabbage (Brassica rapa L.)

Abstract: Similar to radical-induced cell death 1 (SROs) is a family of small proteins unique to plants. SRO transcription factors play an important role in plants’ response to biotic and abiotic stresses. In this study, we identified 12 BrSRO genes in Chinese cabbage (Brassica rapa L.). Among them, a comprehensive overview of the SRO gene family is presented, including physical and chemical characteristics, chromosome locations, phylogenetic analysis, gene structures, motif analysis, and cis-element analyses. The numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…Both cultivated and wild tomatoes SRO genes contained a large number of response elements, including gibberellin, ethylene, abscisic acid, jasmonic acid, and salicylic acid. SRO genes may affect tomato life activities by widely participating in hormone regulation networks, which is consistent with studies in other species ( YongChun et al, 2019 ; Qiao et al, 2020 ). There were also a large number of light-responsive CREs in the SRO promoter region, mainly BOX-4 and G-BOX, and most light-responsive elements were significantly enriched in S. lycopersicum var.…”
Section: Discussionsupporting
confidence: 87%
“…Both cultivated and wild tomatoes SRO genes contained a large number of response elements, including gibberellin, ethylene, abscisic acid, jasmonic acid, and salicylic acid. SRO genes may affect tomato life activities by widely participating in hormone regulation networks, which is consistent with studies in other species ( YongChun et al, 2019 ; Qiao et al, 2020 ). There were also a large number of light-responsive CREs in the SRO promoter region, mainly BOX-4 and G-BOX, and most light-responsive elements were significantly enriched in S. lycopersicum var.…”
Section: Discussionsupporting
confidence: 87%
“…In recent years, a total of 5, 6, 6, 6, 12, and 30 SRO family genes have been identified in rice [ 6 , 21 ], apple [ 19 ], maize [ 22 ], banana [ 23 ], Chinese cabbage [ 24 ], wheat [ 25 ], and tomato [ 26 ], respectively. However, no relevant systematic study about the expression and possible roles of SRO genes in sesame, which has high nutritional quality, but its production is severely threatened by adverse environmental stresses [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the cucumber SRO family genes were identified and cloned, and these genes were named as CsSRO1-CsSRO4, making it a small gene family. The number of SRO family genes was compared to those of previously identified plant species, such as sesame, rice, Arabidopsis, maize, Brachypodium distachyon, tomato, banana, and apple, which generally contained 4-6 SRO genes in their genomes [46,[48][49][50], but was much less than that in Chinese cabbage (12 genes) [51], and wheat (30 genes) [45]. These findings indicated that the expansion of the SRO gene family was relatively conservative, and the number of SRO family genes may not possess an absolute correlation with genome size during plant evolution.…”
Section: Discussionmentioning
confidence: 99%